A luz do sol produz leis mais robustas?: O impacto da transmissão das reuniões de comissão no processo legislativo de Minas Gerais - Luciana Lopes Nominato Braga (2023)
Transparency of legislative proceedings has been advocated by good practices guides and adopted by parliaments around the world, especially in the form of live streaming of committee meetings. Nevertheless, there are controversies about the real effects of transparency, which can be summarized in three groups: “sunshine” which considers the positive impact on accountability, participation and information; “transparency trap”, which points to unintended negative consequences, such as inhibition of debate and consensus building; and “rational ignorance”, which points to the low impact of transparency policies. In 2017, in the middle of the 18th legislature, the Legislative Assembly of Minas Gerais started live transmitting its meetings via Youtube, making possible a natural experiment to compare several proxies of robustness of the legislative process between periods with and without transparency.